Feasible Ubiquitous Innovative Service for Taiwan Resort Industry - Chang, Peggy; Chen, Hong-Bin; Chen, Huan-Tun; Lee, I-Hua (Journal of Asian Business Strategy, 2016)
The Resort Industry is one of the six emerging industries in Taiwan. With changing technology and the rapid development of Information Communication Technology (ICT), how efficiently to combine technology with Resort Industry and how to satisfy customers’ needs of innovative services in an intimate and caring way have become important lessons for the operator. This research is based on eight dimensions and thirty-nine innovative services. According to the result of Delphi method, for the industry, the “Shopping” Dimension is the most feasible innovative service followed by “Leisure” and “Transportation” Dimension. On the other hand, for the Ubiquitous entrepreneur, the most feasible innovation service is “Entertainment” Dimension, secondly are “Shopping” and “Dining” Dimension. Through the corporation of the Ubiquitous Technology (UT) and the industry, the advantages are effectiveness and efficiency, e.g. reducing costs, and increasing operation effectiveness, etc. It has become an important issue in the world of innovative services. Therefore, when technology immerses into the resort industry, it can simplify the complicated working process, optimize the service quality, and increase service efficiency. With above advantages, it provides customize services which bringing the caring and intimate feeling to the customers.